Meta-analysis of the prognostic and clinical value of tumor-associated macrophages in adult classical Hodgkin lymphoma. Issue 1 (December 2016) - Guo, Baoping; Cen, Hong; Tan, Xiaohong; Ke, Qing
Abstract Background The prognostic significance of tumor-associated macrophages (TAM) in adult classical Hodgkin lymphoma (cHL) remains controversial. Here, we report a meta-analysis of the association of CD68 and CD163 infiltration on the clinical outcome of adult cHL. Methods A comprehensive search to identify relevant articles was performed in PubMed, Embase, and Google Scholar on January 31, 2016. Using the fixed effect or random effects model of DerSimonian and Laird, hazard ratios (HR) or odds ratios (OR) with 95 % confidence intervals (CIs) were used as the effect size estimate. Results Twenty-two eligible studies with a total of 2959 patients were identified. Our analysis indicated that a high density of CD68+ TAMs in the tumor microenvironment of adult cHL predicted poor overall survival (OS) (HR: 2.41; 95 % CI, 1.92–3.03), shorter progression-free survival (PFS) (HR: 1.78; 95 % CI, 1.45–2.18), and poor disease-specific survival (HR: 2.71; 95 % CI, 1.38–5.29). High density of CD163+ TAMs in the tumor microenvironment of adult cHL also predicted poor OS (HR: 2.75; 95 % CI, 1.58–4.78) and poor PFS (HR: 1.66; 95 % CI, 1.22–2.27). In addition, we demonstrated that a high density of either CD68+ or CD163+ TAMs was associated with the presence of Epstein-Barr virus in neoplastic cells (ORCD68 : 3.13; 95 % CI, 2.02–4.84; ORCD163 : 2.88; 95 % CI, 1.55–5.34). A high density of either CD68+ or CD163+ TAMs tend to be associated with a more advanced clinical stage (ORCD68 : 1.25; 95 % CI, 0.93–1.67; ORCD163 : 1.19; 95 % CI, 0.86–1.63), B-symptoms (ORCD68 : 1.35; 95 % CI, 0.90–2.01; ORCD163 : 2.19; 95 % CI, 0.96–5.03), higher International Prognostic Factors Project Score (ORCD68 : 1.20; 95 % CI, 0.67–2.15; ORCD163 : 2.00; 95 % CI, 0.92–4.35), and bulky disease (ORCD68 : 1.47; 95 % CI, 0.88–2.47; ORCD163 : 1.19; 95 % CI, 0.72–1.96). Conclusions Our analyses suggest that a high density of either CD68+ or CD163+ TAMs is a robust predictor of adverse outcomes in adult cHL. Increased TAMs should be taken into account to further improve prognostic stratification and the planning of appropriate therapeutic strategies.